2019
DOI: 10.1186/s42269-019-0108-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Bacillus subtilis, B. pumilus, and Pseudomonas fluorescens isolates against root knot nematode Meloidogyne incognita on cowpea

Abstract: Background: Due to the fact that chemical nematicides frequently cause environmental pollution and toxic hazards to human, plants, and domestic animals, certain biocontrol agents of environmentally and toxicologically safe properties and secure to human and animals were tested against root-knot nematode Meloidogyne incognita on cowpea. Objective: The protective effect of two isolates of Bacillus subtilis, B. pumilus, or Pseudomonas fluorescens on M. incognita reproductive parameters infecting cowpea was examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 14 publications
(11 reference statements)
6
17
0
Order By: Relevance
“…The present study also depicted that inoculation of P. aeruginosa (M1) and B. gladioli (M2) improved the morphological characters of the plants inhabited with PPNs. Our studies are in the agreement to previous studies conducted by Abd-El-Khair et al [64], who reported that biocontrol agents Bacillus subtilis, B. pumilus and P. fluorescens had a protective role against PPN M. incognita in improving root length, shoot length, fresh and dry weights in cowpea. According to their assumptions, the biocontrol agents have the stimulating effects on plants by inducing growth, plant nutrition, producing plant hormones and suppressing various pathogens in the surrounding zones [64].…”
Section: Discussionsupporting
confidence: 93%
“…The present study also depicted that inoculation of P. aeruginosa (M1) and B. gladioli (M2) improved the morphological characters of the plants inhabited with PPNs. Our studies are in the agreement to previous studies conducted by Abd-El-Khair et al [64], who reported that biocontrol agents Bacillus subtilis, B. pumilus and P. fluorescens had a protective role against PPN M. incognita in improving root length, shoot length, fresh and dry weights in cowpea. According to their assumptions, the biocontrol agents have the stimulating effects on plants by inducing growth, plant nutrition, producing plant hormones and suppressing various pathogens in the surrounding zones [64].…”
Section: Discussionsupporting
confidence: 93%
“…Bacillus subtilis and B. pumilus caused the highest reduction (82% and 81.8%, respectively) in M. incognita on cowpea [ 32 ]. An isolate of Bacillus megaterium reduced the root penetration and migration of M. graminicola to between 40 and 60% compared with non–treated roots of rice plants [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nematicides provide very effective and faster results by reducing nematode numbers and reproduction rates, but they are not environmentally friendly and have many drawbacks (Abd-El-Khair et al, 2019).…”
Section: Yield (Pod)-related Parametersmentioning
confidence: 99%
“…Trichoderma spp. are basically mycoparasites (Papavizas, 1985), but in recent years, their suppressive effects against plant nematodes have also been reported (Siddiqui and Shaukat, 2004;Javeed et al, 2016;Abd El-Khair et al,2019). Soils rich in organic matter are generally colonized by some biocontrol agents such as T. harzianum that improve biocontrol activity.…”
Section: Introductionmentioning
confidence: 99%